HUBUNGAN KANDUNGAN KLOR SERUM DENGAN HORMON T3/T4 PADA ANAK SEKOLAH DI DAERAH GONDOK ENDEMIK - Sukati Saidin; Djoko Pambudi; Sri Martuti; M. Saidin; Susilowati Herman (Persagi, 2002)
ASSOCIATION OF SERUM CHLOR CONTENT WITH T3/T4 HORMONEIN SCHOOL CHILDREN IN IODINE DEFICIENCY REGION.Background: The National Mapping Survey of IDD (1998) found that 7% of sub districts In Indonesia was regarded as severe endemic goitre area (TGR>30%). The high TGR prevalence, beside as a result of low iodized salt consumption (< 30 ppm), It was assumed as the effect of exposure of goitrogenic agent such as chlorine. Based on observation in Karawang sub district showed people had food habit to consume fish contaminated by insecticide used for killing milk fish predator or salted fish which had also contaminated by insecticide used during process of fish drying. Insecticide raw material consists of chlorine which can not be broken by heat or oxidation. Previous study by Gaitan E. (1986) found that chlorine component could inhibit iodine metabolism to form mono and di-iodotyrosine as precursor of T3 and T4 hormones.Objectives: The aim of this study was to find an association of serum chlorine as a reflection of chlorine consumption from daily food with T3 and T4 hormone.Methods: Research design was case control. Study was conducted in Karawang district, West Java. The subject were elementary school children in the fourth, fifth and sixth grades with positive goitre at grade I and II by palpation. Sample size was 140 children divided into two groups, case group (70 children) and control group (70 children). Main data collected was chlorine consumption from daily food, serum chlorine, serum T3 and T4 hormones as well as anthropometries.Results: The result showed that chlorine consumption from food was relatively greater in case group (135.9 ugr/day) than in control group (129.9 ug/day) but statistically it was not significant. Serum chlorine content in case group (1 14.8 mmol/L) was significantly higher than in control group (102.1 mmol/L). Serum T4 hormone in case group (7.3 ug/dl) was significantly lower than in control group (9.5 ug/dl). Serum T3 hormone in case group (1.83 ng/ml) was significantly lower than in control group (2.3 ng/ml). The association of serum chlorine with T4 hormone was low, r = -0.3488 (p=0.001). The association of serum chlorine with T3 hormone was also low, r = -0.2459 (p=0.051).Conclusions: There is less association of serum chlorine with T 3 and T 4 hormones probably caused by other polutant, such as timbal (Pb) and mercury (Hg).Keywords: serum chlor, T3/T4 hormone, iodine deficiency